New Averaging Method For Risk Reduction In Coastal Region - Nahar, Samsun; Alim, Md. Abdul (Journal of Science & Technology, 2021)
In this paper, a new statistical averaging method (NSAM) has been proposed to solve the multi-objective linear programming problem (MOLPP) by using a new arithmetic averaging method, a new geometric averaging method and a new harmonic averaging method. The statistical averaging method (SAM), which also includes arithmetic averaging, geometric averaging and harmonic averaging, has also been proposed to solve the same MOLPP. All the results obtained by solving the MOLPP using those stated methods have been compared to the results obtained using Chandra Sen’s method which is a well-known technique for making single objective linear programming problem (LPP) from multi-objective LPP.